Combining ability analysis of newly developed monoecious lines of castor (Ricinus communis L.) in Rajasthan: COMBINING ABILITY ANALYSIS OF NEW MONOECIOUS LINES OF CASTOR IN RAJASTHAN - RAMESH; RAKESH CHOUDHARY; MAMTA NEHRA; MANISH KUMAR (Journal of Oilseeds Research, 2021)
Genetic parameters of 50 castor hybrids developed from 10 newly developed monoecious lines and 5 stable pistillate lines were estimated in line x tester design. Analysis of combining ability depicted significant mean sum of squares for both general combining ability (GCA) and specific combining ability (SCA) for all the characters which indicated the presence of both additive and non-additive gene actions. The high amount of s 2 SCA and ratio of GCA to SCA variances near to zero indicated that the dominance gene effect was predominant in newly developed lines for all the characters under study. The highest positive gca effect was exhibited by MCP-1-1, for seed yield and number of capsules on primary raceme, effective length of primary raceme and height up to primary raceme. SKP-84 was also a good general combiner for 100 seed weight, number of capsules on primary raceme, nodes to primary raceme and height up to primary raceme. Among the male parents, MP-11-17 was found the best general combiner for cumulative seed yield, raceme length and numbers of capsules. Cross M-574 x MP-17-17 was the best cross for cumulative seed yield followed by MCP-3 x MP-7-17 and SKP-84 x MP-11-17. These combinations would be useful in breeding programme for improvement in seed yield of castor.